Implementation of Adaptive Neural Fuzzy Inference Systems (Anfis) For Speech Recognition Applications In Smart Home Control - Permana, Roni; Sanjaya, W S Mada; Aliah, Hasniah (Universitas Mandiri, 2024)
Signal Processing is signal processing that is related to the presentation, transformation, and manipulation of signal content and information. Digital Signal Processing is signal processing that is related to the presentation, transformation, and manipulation of signal content and information in digital form. The speech control system is very efficient. Speech signals are signals that change over time at a relatively slow speed. If observed at short intervals (between 5 and 100 miles per second), the practical characteristics are constant, but if observed at longer intervals, the characteristics appear to change according to the sentences spoken. This study uses the signal pattern recognition method with the MFCC and ANFIS methods as learning. The performance results of the entire system obtained an accuracy value with 6 feature extractions in 2 respondents, namely 65% ​​-72.5% and the smarthome control system worked well.